2015
DOI: 10.1371/journal.pone.0138063
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Association between Length of Incarceration and Selected Risk Factors for Non-Communicable Chronic Diseases in Two Male Prisons of Mexico City

Abstract: BackgroundMexico City prisons are characterized by overcrowded facilities and poor living conditions for housed prisoners. Chronic disease profile is characterized by low prevalence of self reported hypertension (2.5%) and diabetes (1.8%) compared to general population; 9.5% of male inmates were obese. There is limited evidence regarding on the exposure to prison environment over prisoner’s health status; particularly, on cardiovascular disease risk factors. The objective of this study is to assess the relatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
11
0
5
Order By: Relevance
“…Three studies reported length of stay to be significantly associated with weight change, but two found that drastic positive changes occur within the first few weeks of incarceration (Clarke and Waring, 2012;Gates andBradford, 2015, Silverman-Retana et al, 2015). Silverman-Retana et al (2015) however observed a U-shaped association between length of stay and BMI change and positive weight change being more prevalent among older inmates. Leigey and Johnston (2015) found longer length of stay to be associated with healthy weight, but one study found that longer stay, greater than one year was associated with higher risk of obesity, seven times higher compared to those who have stayed for shorter periods (AOR 6.92; 95 per cent CI, p < 0.001) (Haysom et al, 2013).…”
Section: Resultsmentioning
confidence: 70%
“…Three studies reported length of stay to be significantly associated with weight change, but two found that drastic positive changes occur within the first few weeks of incarceration (Clarke and Waring, 2012;Gates andBradford, 2015, Silverman-Retana et al, 2015). Silverman-Retana et al (2015) however observed a U-shaped association between length of stay and BMI change and positive weight change being more prevalent among older inmates. Leigey and Johnston (2015) found longer length of stay to be associated with healthy weight, but one study found that longer stay, greater than one year was associated with higher risk of obesity, seven times higher compared to those who have stayed for shorter periods (AOR 6.92; 95 per cent CI, p < 0.001) (Haysom et al, 2013).…”
Section: Resultsmentioning
confidence: 70%
“…Evidence from western countries shows that noncommunicable disease (NCD) is a public health problem in prison [34,35,[41][42][43][44][45]. Recent studies in Africa showed an increased prevalence of NCD among prisoners [44,45].…”
Section: Discussionmentioning
confidence: 99%
“…As desigualdades sociais, a diferença no acesso aos bens e aos serviços, a baixa escolaridade e a desigualdade no acesso à informação determinam, de modo geral, maior prevalência das doenças crônicas e dos agravos decorrentes da evolução dessas doenças (30) . Estudos mostram um aumento na obesidade e nos fatores de risco cardiovascular nas detentas, sugerindo que o encarceramento contribui para o desenvolvimento de doenças crônicas não transmissíveis (31)(32)(33)(34) . Além disso, as detentas têm maior probabilidade de desenvolver sobrepeso e obesidade do que mulheres da população geral e do que os detentos.…”
Section: Discussionunclassified
“…Observou-se, entre as detentas, um consumo baixo de legumes e frutas, menor do que o obsevado na população brasileira em geral. Outros estudos relataram resultados semelhantes (21,32) . Destaca-se que a fonte de alimentos das mulheres detentas avaliadas no presente estudo consistia na dieta ofertada pela instituição penitênciária e por alimentos trazidos por parentes durante as visitas.…”
Section: Discussionunclassified